2013
DOI: 10.1074/jbc.m112.440396
|View full text |Cite
|
Sign up to set email alerts
|

Neural Wiskott-Aldrich Syndrome Protein (N-WASP)-mediated p120-Catenin Interaction with Arp2-Actin Complex Stabilizes Endothelial Adherens Junctions

Abstract: Background: Mechanisms linking cortical actin with adherens junctions (AJs) required for forming restrictive endothelial barrier remain unclear. Results: We show that neural Wiskott-Aldrich syndrome protein (N-WASP) binds AJ constituent, p120-catenin, forms cortical actin, and links AJs with actin. Conclusion: N-WASP stabilizes AJs and thereby maintains endothelial barrier function. Significance: N-WASP represents a novel target for preventing leaky endothelial barrier syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 42 publications
8
56
1
Order By: Relevance
“…Our observation of increased TER following N-WASP depletion conflicts with a previous study, which found the opposite effect: decreased TER following N-WASP depletion in endothelial cells (16). Our studies reveal that the previous result was due to an off target effect of one siRNA in the pool that was used.…”
Section: Depletion Of N-wasp Enhances the Integrity Of The Endothelialcontrasting
confidence: 99%
See 4 more Smart Citations
“…Our observation of increased TER following N-WASP depletion conflicts with a previous study, which found the opposite effect: decreased TER following N-WASP depletion in endothelial cells (16). Our studies reveal that the previous result was due to an off target effect of one siRNA in the pool that was used.…”
Section: Depletion Of N-wasp Enhances the Integrity Of The Endothelialcontrasting
confidence: 99%
“…We observed an increase in the number and staining intensity of longitudinal actin fibers (Fig. 6, upper panels), similar to the previous report (16). In contrast, when we used the pool of three siRNAs (11, 12, and 13, excluding 14), we did not observe this change in actin longitudinal fibers (Fig.…”
Section: N-wasp Controls Endothelial Junction Width and Organization-supporting
confidence: 91%
See 3 more Smart Citations